Developmental teaching tool «Madona» - an alternative to complex tasks - Madona Nikolaishvili (Euro Asian Journal Publishing, 2023)
The article discusses the multifunctional tool of developmental teaching «Madona». The author relies on L. Vygotsky's constructivist theory, according to which learning should precede the child's cognitive development, and offers a universal table, as well as several examples of classroom activities are discussed using the universal tool of educational development «Madona». The author considers that the tool is universal, because it can be used successfully by the student and the teacher. The instrument is a multifunctional chart that is very easy to use. When starting work, the student uses the tool as a plan to complete tasks. It works on the task offered and simultaneously fills in each column. At the end of the work, the table already represents the student's reflections on the work done. The tool develops critical thinking skills and values in accordance with the educational goals provided by the national curriculum: problem-solving skills, critical thinking, creative thinking, communication skills. One of the advantages of the instrument is also the promotion of the development of metacognitive skills
Keywords: Developmental teaching; constructivism; metacognition